Pengaruh ESG Performance dan Debt Maturity Terhadap Efisiensi Investasi - M Rizky Ramadhan; Reni Oktavia; Ratna Septiyanti (BADAN PENERBIT STIEPARI PRESS, 2026)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) performance and debt maturity on investment efficiency in companies listed on the SRI-KEHATI Index during the 2019–2023 period. Investment efficiency is an essential indicator for assessing a company’s ability to allocate capital optimally without leading to overinvestment or underinvestment. The study employs quantitative methods using secondary data obtained from annual reports, the SRI-KEHATI Index, and Bloomberg Terminal. The research sample consists of 24 companies, resulting in 120 firm-year observations selected through purposive sampling. Data analysis was conducted using panel data regression with EViews 12. The results indicate that ESG performance has a positive and significant effect on investment efficiency, implying that companies with better ESG performance tend to make more efficient investment decisions. This finding suggests that strong ESG practices enhance transparency, reduce information asymmetry, and improve corporate governance, leading to optimal capital allocation. Conversely, debt maturity shows no significant effect on investment efficiency, indicating that the short-term debt structure is not yet effective as a disciplinary mechanism for investment decisions among SRI-KEHATI firms. Simultaneously, ESG performance and debt maturity significantly influence investment efficiency. These findings contribute to the literature on investment efficiency in emerging markets and provide practical insights for corporate management and policymakers in optimizing sustainability strategies and debt structure decisions.